Behind the screens Hollywood goes hypercommercial - Allan, James; Doyle, Vincent; Ericsson, Susan; Soar, Matt.; Talreja, Sanjay; Media Education Foundation (Northampton, MA : Media Education Foundation, 2002)
Discusses the idea that mainstream, big-budget movies have become largely a vehicle for advertising and marketing
Product placement : advertising goes to the movies -- Making movies for marketers : cross promotions, merchandising & tie-ins -- Hijacking the movies : Hollywood in an age of conglomerates -- Limiting stories : making movies in a hypercommercial age
Originally produced in 2000
Special features include chapter selection, previews, and subtitle selection
Camera, Susan Ericsson, Vincent Doyle, James Allan, Sanjay Talreja ; editor, Susan Ericsson ; music, Thom Monahan
DVD
Subtitles in English and Spanish
Keywords: Advertising -- Motion pictures -- United States; Motion pictures -- United States -- History